Differences in the Learning Styles of High-achieving Students in Junior High School in West Aceh - Naimatul Qibthiyah Siregar; Masni Masni; Khairuddin Hasan (ISTIFHAM, 2023)
The study aimed to discover high-achieving students' learning styles, similarities and differences, and the most prominent learning styles at MTsN Meureubo and SMPS Darul Aitami. This research uses a comparative method approach. The results showed that the learning styles of outstanding students at MTsN Meureubo were auditory and kinesthetic. Meanwhile, at SMPS Darul Aitami, the learning styles of exceptional students consist of visual, auditory, and kinesthetic learning styles. Students who excel at the two schools receive adequate motivation from their parents or boarding school caretakers, have the habit of reciting before and after sunset prayers, and participate in quizzes or the Olympics. Meanwhile, the difference in the learning styles of outstanding students at MTsN Meureubo and SMPS Darul Aitami is a visual learning style. Students with this visual learning style habitually study before dawn and read classic books at night. The most prominent learning styles of outstanding students at MTsN Meureubo are auditory and kinesthetic. The most prominent learning style at SMPS Darul Aitami is the visual learning style.